Pekerja Anak dan Pendidikannya Di Masa Depan - Hamdani, Febri; Nooraeni, Rani; Lumaksono, Adi (Fakultas Ilmu Pendidikan-Universitas Negeri Malang, 2023)
Child labour has an impact not only on health but also on education in the future. Being a child labour, the minimum consequence is the disruption of the child's time to go to school and in some cases, the child cannot go to school at all. This study uses data from the Indonesia Life Family Survey (IFLS) where the individuals studied are the same for each IFLS period. The results show that there is a difference between those who have worked as child workers in the past, who have a lower level of education than those who were not child laborers. The difference can be seen 14 years later. This is reinforced by the results of statistical tests with Logistic Regression where there is a strong relationship between child labour and the level of final education. Those who are child workers have a greater chance of only graduating from elementary and junior high school compared to those who are not child laborers.